Changes in proteasome activity during postmortem aging of bovine muscle - De Marzo, D.; Nicastro, Francesco; Facciolongo, A.M.; Nicastro, A. (Progress in Nutrition, 2014)
Twelve cross-breed Limousine x Marchigiana beef steers approximately 250 kg live weight were slaughtered. Chilling took place at 2° C and carcasses were allowed to remain in the cooler for 21 days. A portion of the Longissimus dorsi (Ld) muscle was used for determined the activity of two lysosomal enzymes, (Cathepsin D and β-glucuronidase) at 1 hr post-mortem and after 4, 7, 14 and 21 days of aging. Shear force was also determined on the same muscle at each of the above mentioned sampling times. Tenderness improved after 7 days of aging but no significant differences was observed after 14 days. Cathepsin activity was significantly influenced from the aging but not the β-glucuronidase except for the samples from 1 hr vs 21 days (P < 0.05). More research is need to verify these findings.